Perylenediimides as non-fullerene acceptors in bulk-heterojunction solar cells (BHJSCs). Issue 24 (23rd May 2016) - Fernández-Lázaro, Fernando; Zink-Lorre, Nathalie; Sastre-Santos, Ángela
Abstract : Perylenediimides are ideal candidates for the substitution of fullerene derivatives as electron acceptors in bulk heterojunction organic solar cells due to their extremely intense light absorbance, high electron mobility and excellent photochemical stability. Abstract : Perylenediimides are ideal candidates for the substitution of fullerene derivatives as electron acceptors in bulk heterojunction organic solar cells due to their extremely intense light absorbance, high electron mobility and excellent photochemical stability. In this review article, we briefly highlight the recent progress in highly efficient perylenediimide dyes characterized by a reduction of the cofacial stacking without an adverse impact in their charge-transport properties, which has led to PCEs higher than 8.4%.